Unveiling the Kuznets curve in elderly road deaths: the impact of economic growth, income inequality and urbanization - Yang, Kun; Law, Teik Hua; Megat-Johari, Megat Usamah; Hu, Qizhou (Taylor and Francis, 2026)
Prior research showed a reverse U-shaped or Kuznets curve association between road deaths and income growth. However, no research has linked income growth to elderly road deaths (ERD). This study uses the fixed effects negative binomial panel regression on 82 countries over 30 years to close this gap. Results show a Kuznets curve association between the ERD rate and per capita Real Gross Domestic Product (RGDP). The ERD rate rises with per capita RGDP to a threshold, and then declines as income continues to grow. Additionally, increasing income disparity delays this critical turning point associated with increasing per capita RGDP. This study also reveals a reverse U-shaped association between urbanization (URB) and ERD rate, with ERD rate peaking in countries with diverse traffic conditions and less road choice. Considering economic and demographic changes, this study emphasises the need for ERD rate reduction policies.